Comprehensive epidemiological profiling of poultry-derived Salmonella spp. in Shandong, China, 2019–2022: a longitudinal study of prevalence, antibiotic resistances, virulence factors and molecular characteristics - Chen, Lele; Shi, Yuxia; Wang, Minge; Li, Yubao; Si, Zhenshu (Frontiers in Microbiology, 2025)
Salmonella spp., as a major foodborne pathogen, pose significant threats to public health globally and has been an important zoonotic contamination for poultry industry that should receive increasing attentions. This study aimed to comprehensively investigate the prevalence, antimicrobial resistances, virulence factors, and plasmid types of Salmonella isolates collected from chickens, ducks, and geese across eight cities in Shandong between 2019 and 2022. Out of 300 samples, 53 Salmonella strains (17.67%) were isolated, with varied prevalence from 8.33% to 25.00% in different cities of Shandong. A total of seven serotypes were identified among the 53 Salmonella isolates, wherein the S. Enteritidis (45.28%), S. Pullorum (22.64%) and S. Typhimurium (16.98%) were identified as the most prevalent. Whole-genome sequencing analysis revealed that ST11, ST92, and ST19 were the predominant sequence types for S. Enteritidis, S. Pullorum, and S. Typhimurium, respectively. Phylogenetic analysis indicated that potential clonal spread of S. Enteritidis, S. Pullorum, and S. Typhimurium occurred across different regions, particularly the evidences supported that the S. Typhimurium isolates were dispersed in a cross-species manner. Finally, the phenotypic and genotypic profiling of antibiotic resistance among the isolates revealed that these isolates were multidrug resistant with corresponding antibiotic resistance genes (ARGs) including blaTEM, aac, aph, tet(A), and tet(B) to confer them with resistances to commonly-used veterinary drugs such as β-lactams, quinolones, macrolides. To sum, this study provides valuable insights into the current epidemiology of Salmonella in poultry industry in one of the biggest provinces in China, and shedding the light on the urgent necessity for further approaches to prevent and decontaminate such MDR Salmonella in livestock under One Health concept.